2003
DOI: 10.1002/gcc.10217
|View full text |Cite
|
Sign up to set email alerts
|

Novel heteroplasmic frameshift and missense somatic mitochondrial DNA mutations in oral cancer of betel quid chewers

Abstract: Mitochondrial DNA (mtDNA) has been proposed to be involved in carcinogenesis because of its high susceptibility to oxidative DNA damage and limited repair mechanisms. For investigation of the potential role of somatic mtDNA mutations in the tumorigenesis of oral cancer, we screened the occurrence of mtDNA mutations by the temporal temperature gradient gel electrophoresis method. We amplified the entire mitochondrial genome by use of 32 pairs of overlapping primers, and to identify the mutations, we sequenced D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
3
41
1
Order By: Relevance
“…They found all mtDNA mutations in a part of the D-Loop and a mtDNA microsatellite instability, defined as insertions or deletions in the D310 repeat, in 42% of the tumours. Another study showed 66% of D-Loop mutations in 18 oral cancers of betel quid chewers (Tan et al, 2003), which however cannot be really assimilated to HNSCC of tobacco and alcohol consumers. The vast majority of these mutations were located between nucleotides 204 and 489 and 44% of the tumours harboured mutations in the D310 repeat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found all mtDNA mutations in a part of the D-Loop and a mtDNA microsatellite instability, defined as insertions or deletions in the D310 repeat, in 42% of the tumours. Another study showed 66% of D-Loop mutations in 18 oral cancers of betel quid chewers (Tan et al, 2003), which however cannot be really assimilated to HNSCC of tobacco and alcohol consumers. The vast majority of these mutations were located between nucleotides 204 and 489 and 44% of the tumours harboured mutations in the D310 repeat.…”
Section: Discussionmentioning
confidence: 99%
“…Betel quid contains tender areca nuts and lime that have been shown to generate ROS and induce oxidative DNA damage (Nair et al, 1987;Stich and Anders, 1989), which can initiate or promote oral carcinogenesis. These betel quid compounds could therefore preferentially target mtDNA, which may explain the high proportion of oral tumours with mtDNA mutation observed in betel quid chewers (Tan et al, 2003), compared to that observed in cigarette smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A female carrying a pathogenic mtDNA mutation is at risk of passing the mutation to her offspring, even if she is asymptomatic with low-level heteroplasmy in somatic cells. In addition, there is growing evidence that somatic mtDNA alterations are associated with aging and a variety of common diseases, including diabetes and cancers (5)(6)(7)(8)(9)(10).…”
Section: © 2012 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Somatic mtDNA alterations have been reported in many types of cancers and may play a role in tumorigenesis (5,(32)(33)(34)(35). However, relatively few cancers harbor detectable deleterious somatic mtDNA mutations (6,36,37 ). This hypothesis may be tested by using the deep sequencing approach which, in theory, reaches a level of detection equivalent to singlemolecule analysis.…”
Section: Limit Of Detection Of Mtdna Heteroplasmymentioning
confidence: 99%